Desire thinking as a predictor of drinking status following treatment for alcohol use disorder: A prospective study. (August 2019) - Martino, Francesca; Caselli, Gabriele; Fiabane, Elena; Felicetti, Federica; Trevisani, Cecilia; Menchetti, Marco; Mezzaluna, Clarice; Sassaroli, Sandra; Albery, Ian P.; Spada, Marcantonio M.
Abstract: Research has indicated that craving is one of the strongest predictors of treatment outcome and relapse in Alcohol Use Disorders (AUD) but there is little consensus on the factors that may influence its activation and escalation. Research has also shown that desire thinking is an important cognitive process which may exacerbate craving in problem drinkers. The aim of present study was to explore, for the first time, the role of desire thinking in prospectively predicting relapse, craving and binge drinking in patients receiving treatment for AUD. One hundred and thirty-five patients admitted to two rehabilitation centres and two outpatient services for addiction and mental health problems were administered baseline, treatment completion and three months follow-up measures of anxiety and depression, AUD severity, binge drinking frequency, craving and desire thinking. Results indicated that the verbal perseveration component of desire thinking at treatment completion was the only significant predictor of relapse at follow-up over and above baseline AUD severity and binge drinking frequency. Furthermore, the imaginal prefiguration component of desire thinking and craving levels at treatment completion were found to predict craving levels at follow-up independently of AUD severity and binge drinking frequency at baseline. Finally, both the imaginal prefiguration and verbal perseveration components of desire thinking at treatment completion were found to be the only predictors of binge drinking frequency at follow-up independently of AUD severity and binge drinking frequency at baseline. Treatments for AUD should aim to reduce desire thinking in people to enhance clinical outcomes and reduce relapse risk. Highlights: Verbal perseveration at treatment completion predicted relapse at follow-up independently of baseline variables. Imaginal prefiguration and craving levels at treatment completion predicted craving levels at follow-up independently of baseline variables. Imaginal prefiguration and verbal perseveration at treatment completion predicted binge drinking frequency at follow-up independently of baseline variables. Treatments for AUD should aim to reduce desire thinking in people to enhance clinical outcomes and reduce relapse risk.